2018
DOI: 10.1080/10888691.2018.1484746
|View full text |Cite
|
Sign up to set email alerts
|

Why do extracurricular activities prevent dropout more effectively in some high schools than in others? A mixed-method examination of organizational dynamics

Abstract: This study describes policies and practices implemented in 12 high schools (Quebec, Canada) that more or less effectively leveraged extracurricular activities (ECA) to prevent dropout among vulnerable students. Following an explanatory sequential mixed design, three school profiles (Effective, Ineffective and Mixed) were derived based on quantitative studentreported data. Qualitative interviews with frontline staff revealed that in Effective schools, ECA had a unique overarching goal: to support school engagem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…According to previous research findings regarding extracurricular activities (i.e., a nonmandatory activity organized by the school outside of class periods) as a means to prevent high school dropout and aspire the pursuit of postsecondary education (Farb & Matjsako, 2012), we wanted to test how science students' involvement in scientific extracurricular activities could predict and enhance academic-specific outcomes. To date, extracurricular activities have provided evidence of increased incentive to attend school , school perseverance (McCabe et al, 2018), as well as generalization effects of motivation to the school context (Denault & Guay, 2017); however, no studies to date have examined which motivational factors predict students' involvement in extracurricular activities and its potential impact on academic performance. Such studies are important because they provide a richer understanding of the extent to which academic and psychological factors influence students' pursuit of STEM programs in higher education.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous research findings regarding extracurricular activities (i.e., a nonmandatory activity organized by the school outside of class periods) as a means to prevent high school dropout and aspire the pursuit of postsecondary education (Farb & Matjsako, 2012), we wanted to test how science students' involvement in scientific extracurricular activities could predict and enhance academic-specific outcomes. To date, extracurricular activities have provided evidence of increased incentive to attend school , school perseverance (McCabe et al, 2018), as well as generalization effects of motivation to the school context (Denault & Guay, 2017); however, no studies to date have examined which motivational factors predict students' involvement in extracurricular activities and its potential impact on academic performance. Such studies are important because they provide a richer understanding of the extent to which academic and psychological factors influence students' pursuit of STEM programs in higher education.…”
Section: Studymentioning
confidence: 99%
“…Additionally, we postulated that involvement in scientific extracurricular activities would be related only to those experiencing HP (not OP) as they would have adopted a flexible approach with their studies and not be exclusively focused on academic performance. Moreover, we also expected involvement in scientific extracurricular activities to be associated with academic performance in science courses based on past research leveraging associations between extracurricular activities and school perseverance (Denault & Poulin, 2017;Eccles & Roeser, 2009;McCabe et al, 2018;Thouin et al, 2018). Finally, we measured university science program applications instead of intentions.…”
Section: Studymentioning
confidence: 99%
“…The adults who lead these activities often serve as important role models -many of them had positive experiences with these activities themselves and want to provide their own students with similar experiences (Quiroz, 2000;Shulruf, 2010). Moreover, ECA sponsors often work with the same students over a span of years, allowing them to build trusting relationships with them (Anderson et al, 2004;Eldridge et al, 2014) and, over time, to help them develop the skills and dispositions needed for academic, social, and vocational success (McCabe et al, 2020;Roth & Brooks-Gunn, 2016).…”
Section: Social Cultural and Academic Benefitsmentioning
confidence: 99%
“…Researchers have often found that the most effective school leaders tend to unite all members of the organization -from teachers to administrators, counselors, secretaries, custodians, and on and on -around a shared definition of the school's mission and values, so that they understand how their individual efforts contribute to the whole (Hallinger & Heck, 2010;McCabe et al, 2020). But even effective leaders often overlook their ECAs, failing to see that they, too, can be integral to the school's larger priorities.…”
Section: Define Clear and Coherent Goalsmentioning
confidence: 99%
“…Additionally, we postulated that involvement in scientific extracurricular activities would be related only to those experiencing HP (not OP) as they would have adopted a flexible approach with their studies and not be exclusively focused on academic performance. Moreover, we also expected involvement in scientific extracurricular activities to be associated with academic performance in science courses based on past research leveraging associations between extracurricular activities and school perseverance (Denault & Poulin, 2017;Eccles & Roeser, 2009;McCabe et al, 2018;Thouin et al, 2018). Finally, we measured university science program applications instead of intentions.…”
Section: Studymentioning
confidence: 99%